LINEN RENTAL LAUNDRY MARKETING PLAN WITH RFID TECHNOLOGY - Zulhamiadi M; Rhian Indradewa; Sukmo Hadi Nugroh; Muhammad Dhafi Iskandar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Marketing activities are a company planning tool that has been made to meet company goals. One of the plans that the company uses is to use a marketing mix strategy in introducing its products. In our writing about the laundry industry business plan with the title LINEN RENTAL LAUNDRY WITH RFID TECHNOLOGY. RFID (Radio Frequency Identification) is a wave-based identification technology using a means called an RFID tag to retrieve remote data. RFID has a very important part which is the frequency tag and tag reader. The tag reader reads the signal emitted by the RF. The tag responds by reemitting data including a unique serial number. When determining the target market that is suitable for the type and scale of the business. PT Think Clean Laundry must understand customer needs, expectations, and preferences, and offer added value that can differentiate PT Think Clean Laundry from competitors. Build strong and professional branding. demonstrate the quality, speed, and reliability of the service, and use social media, using state-of-the-art, well-maintained, and environmentally friendly equipment. PT. Think Clean Laundry should choose washing machines, irons/steams, and materials that can produce clean, hygienic, and neat clothes or textiles, while saving operational costs and reducing environmental impact. With the determination of marketing or sales planning, the business will be declared runnable and can be seen more clearly. Marketing planning is an activity that must be carried out and planned carefully so that it can see whether a business can and should be run or not. With this marketing or sales planning, it is hoped that the company can predict the right marketing method, and be able to ensure the sustainability of the company due to maximum sales. In this study, it was found that marketing planning is needed to understand the company's potential, targets and needs, expectations and desires of customers. Therefore, marketing/sales planning is the spearhead of a business and determines whether a business can and should be run, maintained and predicts the sustainability of a business.